Pengaruh Bentuk Permukaan Heat Absorber Plate terhadap Temperatur dan Waktu Pengeringan pada Solar Dryer Kemiri - Mietra Anggara; Rita Desiasni (Universitas Muhammadiyah Metro, 2019)
Candlenut (Aleurites moluccana Wild) is an important versatile plant in Indonesia. Batulanteh Subdistrict, Batu Dulang Village is the highest candlenut producer in Sumbawa Regency, NTB with a land area of 595.7 ha and total production of 285.17 tons. Post-harvest candlenut handling at the farmer's level is still done traditionally where drying candlenuts on the floor or para-finished needs to be done with solar dryers. In this research, testing on absorbent plates is flat and corrugated as well as natural drying. The results showed that the corrugated heat absorber plate had the highest temperature average of 86.84 oC with a drying time of 8 hours with the amount of hazelnut water content of 6.12%. Making zinc absorbent plates is more effective and efficient used to dry candlenut in increasing the production of candlenuts. Key words: Candlenut, solar dryer, absorbent plate, Candlenut water content